2011
DOI: 10.1007/s11207-011-9732-7
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Observation of Oscillations in the Corona During the Total Solar Eclipse of 22 July 2009

Abstract: We performed high resolution spectroscopy of the solar corona during the total solar eclipse of 22 July 2009 in two emission lines: the green line at 5303 Å due to Fe XIV and the red line at 6374 Å due to Fe X, simultaneously from Anji (latitude 30°28.1 N; longitude 119°35.4 E; elevation 890 m), China. A two-mirror coelostat with 100 cm focal length lens produced a 9.2 mm image of the Sun. The spectrograph using 140 cm focal length lens in Littrow mode and a grating with 600 lines per millimeter blazed at 2 µm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…Banerjee et al (2009) reported the possible presence of propagating torsional Alfvén waves in polar coronal holes, as manifested by the non-thermal broadening of emission lines. A similar interpretation can be made for the nonthermal broadening of coronal lines observed during an eclipse (Singh et al 2011). Torsional Alfvén waves were also proposed as one possible explanation of the transverse motions of coronal rain plasmas observed by Hinode/SOT (Antolin & Verwichte 2011).…”
Section: Introductionsupporting
confidence: 61%
“…Banerjee et al (2009) reported the possible presence of propagating torsional Alfvén waves in polar coronal holes, as manifested by the non-thermal broadening of emission lines. A similar interpretation can be made for the nonthermal broadening of coronal lines observed during an eclipse (Singh et al 2011). Torsional Alfvén waves were also proposed as one possible explanation of the transverse motions of coronal rain plasmas observed by Hinode/SOT (Antolin & Verwichte 2011).…”
Section: Introductionsupporting
confidence: 61%
“…Recently, Raju, Chandrasekhar, and Ashok (2011) reported an increase in the line width of the green line with height, up to about 400 ′′ above the limb, from the line profiles obtained during the total solar eclipse of 21 June 2001 using a Fabry-−Perot [FP] etalon. Singh et al (2011) also observed a case where the green-line width increases with height and showed that the FWHM of emission lines is different for different coronal features. By analysing over 130 coronal structures Singh et al (2003b) observed that 89 % of the structures show a negative gradient in the green emission line and 95 % of those show a positive gradient in the red emission line.…”
Section: Introductionmentioning
confidence: 87%
“…Lateral transverse oscillations are often interpreted as fast-mode kink waves or Alfvén waves. The ubiquitous presence of transverse waves has been observed in chromospheric spicules and mottles Singh et al 2007;Zaqarashvili et al 2007; Kukhianidze et al 2006;Kim et al 2008;He et al 2009b;Okamoto & De Pontieu 2011;Kuridze et al 2012), coronal loops (Aschwanden et al 1999;Nakariakov et al 1999;Nakariakov & Ofman 2001;Verwichte et al 2004;Tomczyk et al 2007;Tomczyk & McIntosh 2009;McIntosh et al 2011;Singh et al 2011), and plume-like structures in different regions of the Sun (McIntosh et al 2011;Tian et al 2011b). Case studies suggest that some transverse waves are likely associated with impulsive phenomena such as flare activities, filament eruptions, or coronal mass ejections (CME) (Aschwanden et al 1999(Aschwanden et al , 2002Schrijver et al 2002;Wang et al 2004;O ′ Shea et al 2007b;Chen et al 2008;Ofman & Wang 2008;He et al 2009a;Verwichte et al 2010b;Aschwanden & Schrijver 2011;Pietarila et al 2011;Liu et al 2011Wang et al 2012b).…”
Section: Introductionmentioning
confidence: 99%